The RANO Leptomeningeal Metastasis Group proposal to assess response to treatment: lack of feasibility and clinical utility and a revised proposal. Issue 5 (23rd January 2019) - Le Rhun, Emilie; Devos, Patrick; Boulanger, Thomas; Smits, Marion; Brandsma, Dieta; Rudà, Roberta; Furtner, Julia; Hempel, Johann-Martin; Postma, Tjeerd J; Roth, Patrick; Snijders, Tom J; Winkler, Frank; et al.
Abstract: Background: A scorecard to evaluate magnetic resonance imaging (MRI) findings during the course of leptomeningeal metastases (LM) has been proposed by the Response Assessment in Neuro-Oncology (RANO) group. Methods: To explore the feasibility of the Leptomeningeal Assessment in Neuro-Oncology (LANO) scorecard, cerebrospinal MRIs of 22 patients with LM from solid tumors were scored by 10 neuro-oncologists and 9 neuroradiologists at baseline and at follow-up after treatment. Raters were blinded for clinical data including treatment. Agreement between raters of single items was evaluated using a Krippendorff alpha coefficient. Agreement between numerical parameters such as scores for changes between baseline and follow-up and total scores was evaluated by determining the intraclass coefficient of correlation. Results: Most raters experienced problems with the instructions of the scorecard. No acceptable alpha concordance coefficient was obtained for the rating of single items at baseline or follow-up. The most concordant ratings were obtained for spinal nodules. The concordances were worst for brain linear leptomeningeal enhancement and cranial nerve enhancement. Discordance was less prominent among neuroradiologists than among neuro-oncologists. High variability was also observed for evaluating changes between baseline and follow-up and for total scores. Conclusions: Assessing response of LM by MRI remains challenging. Central imaging review is therefore indispensable for clinical trials. Based on the present results, we propose a new, simplified scorecard that will require validation using a similar approach as pursued here. The main challenges are to define measurable versus nonmeasurable (target) lesions and measures of change that allow assessment of response.